Polymerization of fibrin: direct observation and quantification of individual B:b knob-hole interactions - Litvinov, Rustem I. (American Society of Hematology, 2007)
The polymerization of fibrin occurs primarily through interactions between N-terminal A- and B-knobs, which are exposed by the cleavage of fibrinopeptides A and B, respectively, and between corresponding a- and b-holes in the γ- and β-modules. Of the potential knob-hole interactions—A:a, B:b, A:b, and B:a—the first has been shown to be critical for fibrin formation, but the roles of the others have remained elusive. Using laser tweezers–based force spectroscopy, we observed and quantified individual B:b and A:b interactions. Both desA-fibrin with exposed A-knobs and desB-fibrin bearing B-knobs interacted with fragment D from the γD364H fibrinogen containing b-holes but no functional a-holes. The strength of single B:b interactions was found to be 15 to 20 pN, approximately 6-fold weaker than A:a interactions. B:b binding was abrogated by B-knob mimetic peptide, the (β15-66)(2) fragment containing 2 B-knobs, and a monoclonal antibody against the β15-21 sequence. The interaction of desB-fibrin with fragment D containing a- and b-holes produced the same forces that were insensitive to A-knob mimetic peptide, suggesting that B:a interactions were absent. These results directly demonstrate for the first time B:b binding mediated by natural B-knobs exposed in a fibrin monomer.